The Structural Basis for Activation and Inhibition of ZAP-70 Kinase Domain - Huber, Roland G.; Fan, Hao; Bond, Peter J. (PLOS Computational Biology, 2015)
Author Summary ZAP–70 is a key protein kinase in the adaptive immune system. It is essential for development and function of T cells and natural killer cells, and associated mutations can lead to conditions such as severe combined immunodeficiency (SCID). Here, simulations of the ZAP–70 kinase domain are used to study its dynamics in response to different mechanistic signals. We identify crucial motions over microsecond timescales, which help to rationalize in atomic detail previous structural and experimental data regarding its biological regulation. We subsequently propose a scheme for the phosphorylation-dependent activation cascade of ZAP–70, and for its ligand-dependent inhibition. Finally, we characterize a novel cryptic pocket adjacent to the active site and activation loop, which is distinct from classical type I or type II kinase sites. The pocket is in close proximity to several residues whose mutations cause SCID in humans, and its identification offers promise in future drug design efforts.